The X-linked inhibitor of apoptosis regulates long-term depression and learning rate - Gibon, Julien (2016)
Hippocampal long-term depression (LTD) is an active form of synaptic plasticity that is necessary for consolidation of spatialmemory, contextual fearmemory, and novelty acquisition. Recent studies have shown that caspases (CASPs) play an important role in NMDA receptor-dependent LTD and are involved in postsynaptic remodeling and synaptic maturation. In the present study, we examined the role of X-linked inhibitor of apoptosis (XIAP), a putative endogenous CASP inhibitor, in synaptic plasticity in the hippocampus. Analysis in acute brain slices and in cultured hippocampal neurons revealed that XIAP deletion increases CASP-3 activity, enhances α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor internalization, sharply increases LTD, and significantly reduces synapse density. In vivo behaviors related to memorywere also altered in XIAP-/- mice, with faster acquisition of spatial object location and increased fear memory observed. Together, these results indicate that XIAP plays an important physiologic role in regulating sublethal CASP-3 activity within central neurons and thereby facilitates synaptic plasticity and memory acquisition.